The mechanism of universal green antisolvents for intermediate phase controlled high-efficiency formamidinium-based perovskite solar cells. Issue 3 (18th December 2019) - Wang, Luyao; Wang, Xin; Deng, Lin-Long; Leng, Shibing; Guo, Xiaojun; Tan, Ching-Hong; Choy, Wallace C. H.; Chen, Chun-Chao
Abstract : Tuning the polarity of green antisolvents (using various ethers) allows high control over the purity of the intermediate phase of triple-cation lead halide perovskite thin films. Abstract : Antisolvent-assisted crystallization is adopted widely in the preparation of double-cation [ e.g., cesium/formamidinium (Cs/FA), formamidinium/methylammonium (FA/MA)] and triple-cation ( e.g., Cs/FA/MA) FA-based perovskite solar cells (PSCs) to enhance their power conversion efficiencies (PCEs) and device stability. Although many antisolvents have been applied to treat various perovskites with different compositions, their crystallization mechanisms have remained unclear. In this study, we investigated the effects of a series of green antisolvents—namely, the ethers diethyl ether, anisole, diisopropyl ether (DIE), and dibutyl ether—on the crystallization of perovskites. We found that the formation of an intermediate phase was heavily determined by the antisolvent's polarity. Indeed, through judicious control of the antisolvent's polarity, it was possible to form a pure intermediate phase, without a PbI2 or perovskite phase. Upon thermal annealing, the crystallization of perovskites was improved. Understanding the mechanism of formation of the intermediate phase led us to identify DIE as a green antisolvent with universal perovskite compatibility, achieving champion PCEs of 20.05%, 20.15%, and 21.26% for Cs/FA, FA/MA, and Cs/FA/MA, respectively. The PCE of large-area (1 cm 2 ) PSCs reached 18.51%. Furthermore, the repeatability of these champion PCEs was greatly improved. This work contributes to the understanding of antisolvent's polarity as an important factor affecting the formation of a pure intermediate phase of FA-based perovskites, which also offers a greener approach for the production of PSCs.